The conscious mind : in search of a fundamental theory - Chalmers, David John (Oxford University Press, 1996)
What is consciousness? How do physical processes in the brain give rise to the self-aware mind and to feelings as profoundly varied as love or hate, aesthetic pleasure or spiritual yearning? These questions today are among the most hotly debated issues among scientists and philosophers, and we have seen in recent years superb volumes by such eminent figures as Francis Crick, Daniel C. Dennett, Gerald Edelman, and Roger Penrose, all firing volleys in what has come to be called the consciousness wars. Now, in The Conscious Mind, philosopher David J. Chalmers offers a cogent analysis of this heated debate as he unveils a major new theory of consciousness, one that rejects the prevailing reductionist trend of science, while offering provocative insights into the relationship between mind and brain.